2018
DOI: 10.1142/s0219876218500378
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Different Tip Clearances Effect on the Hydrodynamic Performance of Pumpjet Propulsor

Abstract: Previous studies show that the tip clearance loss limits the improvement of turbomachinery performance, and it is roughly in close relation with the gap size. In this study, a pumpjet propulsor (PJP) with different sizes of tip clearances (δ = 0.2, 0.5, 1, 2, 3 mm) has been presented to investigate the influence of tip clearances on PJP. This analysis is based on computational fluid dynamic (CFD) method, and the SST k-ω turbulence model is applied. Calculations are carried out with a worldwide employed ducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The RANS equations are adopted herein. Moreover, the SST k − ω turbulence model is used in the study of traditional propellers [43,44] and the research of PJP [5,12,[14][15][16]19,45,46]. The previous studies have shown that the SST k − ω turbulence model has good applicability in the numerical simulation of the PJP.…”
Section: The Basic Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The RANS equations are adopted herein. Moreover, the SST k − ω turbulence model is used in the study of traditional propellers [43,44] and the research of PJP [5,12,[14][15][16]19,45,46]. The previous studies have shown that the SST k − ω turbulence model has good applicability in the numerical simulation of the PJP.…”
Section: The Basic Equationmentioning
confidence: 99%
“…The SST k − ω turbulence model has a strong applicability as the turbulent shear stress evacuation process is also considered in the definition of the turbulent viscosity process. The author compared the hydrodynamic performance differences of the PJP among the three turbulence models: SST k − ω, standard k − ε, and Realizable k − ε turbulence model [45]. They showed that that the SST k − ω turbulence model afforded the smallest hydrodynamic performance errors.…”
Section: The Basic Equationmentioning
confidence: 99%
“…As observed in Figures 7 to 9, the coefficients of thrust, torque, and efficiency decrease with increasing tip clearance size, but at tip clearance size of 0.0125 (6.25% of the propeller radius), there is a deflection in the diagram of torque and torque. According to the review of articles related to the size of tip clearance in pump jet and ducted propeller, the standard dimensions are less than 6% of the rotor diameter 30,31 and at larger sizes of tip clearance, the impact of duct presence on the system performance disappears. As a result, it is not possible to give a definite opinion about tip sizes larger than 6% of the rotor diameter.…”
Section: Numerical Analysis Of Linear Jet Systemmentioning
confidence: 99%
“…The tip clearance is a key factor for the shrouded rotor and has been a research hotspot for PJP. The authors of [18][19][20][21] numerically investigated the influence of tip clearance on post-stator PJP. Results showed that efficiency is closely related to the size of clearance due to the energy loss generated by tip leakage vortex (TLV).…”
Section: Introductionmentioning
confidence: 99%